Online Course on Potato Production for Georgia: Final Technical Report (FTR) - Bentley, J.W.; Andrade-Piedra, J.L. (International Potato Center, 2022)
The Online Course on Potato Production for Georgia was held to strengthen the potato seed production capacities of local and national technicians in the USAID Potato Program in Georgia. The virtual course was funded by USAID and organized by the International Potato Center (CIP) covering the following topics: pest and disease management, seed production, and fertilizer and water management. The course was organized around six online webinars and six discussion sessions using CIP’s Talent MS platform. Each webinar and discussion session took between 60 and 90 minutes. The online webinars included a pre-recorded presentation and a Q&A session led by the course instructors. The webinars were prepared in English by the course instructors (with input from the course organizers) and were translated (text and voice over) into the Georgian language. The discussion sessions mainly included panels, with the instructors asking questions to stimulate discussion, and responses from the participants or students (farmers, business people, extensionists and researchers). There was simultaneous English-Georgian translation for all Q&A and discussion sessions. About half of the course participants were women. The online webinars were held over six consecutive weeks (1 June—7 July), usually on Tuesdays (two webinars were held on Wednesdays). The discussion sessions took place that same week on Thursday. A 10-question, multiple-choice test was given at the start of each webinar and near the end of each discussion session (one unique test each week) to judge how well the participants mastered the course material. Students who attended at least five webinars and five discussion sessions received a certificate of participation. The six units were: Unit 1: Integrated management of late blight - Wilmer Pérez Unit 2: Integrated management of viral diseases - Segundo Fuentes Unit 3: Plant nutrition and fertilizer management – Elke Vandamme Unit 4: Postharvest and seed potato storage – André Devaux Unit 5: Production of seed potato - Jorge Andrade-Piedra Unit 6: Irrigation and water management – David Ramírez and Javier Rinza At the end of week 6, the participants evaluated the course, suggesting that they thought that the content, instructors and format were of high quality.